2011
DOI: 10.5539/gjhs.v3n2p162
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Tetrahydrofolate Reductase Gene Polymorphism and the Risk of Ischemic Stroke in Type 2 Diabetic Egyptian Patients

Abstract: Background: A common C677T mutation of methylenetetrahydrofolate reductase (MTHFR) gene is reported to be associated with hyperhomocysteinemia a risk for atherosclerotic vascular diseases and ischemic stroke (IS). Aim: To clarify the possible role of the MTHFR 677C>T polymorphism in predisposition to IS and to assess the relationship of allelic variants of MTHFR gene with homocysteine (Hcy) plasma levels and other risk factors of atherosclerosis and IS in type 2 diabetic Egyptians. Subjects: Group I: 40 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Many studies, however, included cases with T2DM and serious complications, even when the study purported to assess only the association between the MTHFR SNP and T2DM per se. Therefore we divided the 39 studies into two subgroups: 14 studies that explicitly reported the presence of serious complications among cases or failed to report on such complications at all [8], [21], [22], [27], [28],[30],[43],[45],[46],[48],[50],[51],[58],[60], and 25 studies that explicitly reported the absence of serious complications [7], [26], [29], [31]–[42], [44], [47], [49], [52][57], [59]. Meta-analysis of these two subgroups, like the meta-analysis across all included studies, failed to provide clear, consistent evidence that the genotype at MTHFR polymorphism rs1801133 was associated with either increased or reduced risk of T2DM (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies, however, included cases with T2DM and serious complications, even when the study purported to assess only the association between the MTHFR SNP and T2DM per se. Therefore we divided the 39 studies into two subgroups: 14 studies that explicitly reported the presence of serious complications among cases or failed to report on such complications at all [8], [21], [22], [27], [28],[30],[43],[45],[46],[48],[50],[51],[58],[60], and 25 studies that explicitly reported the absence of serious complications [7], [26], [29], [31]–[42], [44], [47], [49], [52][57], [59]. Meta-analysis of these two subgroups, like the meta-analysis across all included studies, failed to provide clear, consistent evidence that the genotype at MTHFR polymorphism rs1801133 was associated with either increased or reduced risk of T2DM (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in the present systematic review did not analyze Hcy levels in cases and controls, making it difficult to gain a comprehensive picture. Of the studies that did examine whether Hcy levels were associated with the rs1801133 polymorphism, 11 found the TT genotype to be associated with higher Hcy levels than the CT or CC genotypes in patients with T2DM [7], [8], [31], [32], [35], [45], [46], [51], [54], [59], [60], while 6 found no such association [27], [48], [49], [52], [56], [57]. A meta-analysis published in 1998 concluded there was an association between the TT genotype and elevated plasma homocysteine levels in individuals with T2DM [17], while a more recent prospective study found no such association [72].…”
Section: Discussionmentioning
confidence: 99%